1977
DOI: 10.3758/bf03197583
|View full text |Cite
|
Sign up to set email alerts
|

The effects of complexity on confidence ratings in linguistic integration

Abstract: Bransford and Franks (1971) introduced a paradigm for the study of linguistic integration. Their primary measure was subjects' rated confidence in their responses. The present paper considers the appropriateness of this dependent variable, and concludes that the relation between sentence complexity and rated confidence is too small and unstable to justify the emphasis which confidence ratings have received. Further, certain differences between concrete and abstract sentences were obscured by a confidence anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Neither were the results due to subjects employing response biases or adopting guessing strategies. Although these criticisms have been aimed toward some of the language-based studies (Clifton, Kurcz, & Jenkins, 1965;Hayes-Roth & Hayes-Roth, 1977;James, Hillinger, & Murphy, 1977;Soli & Balch, 1976), none of them are warranted here.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Neither were the results due to subjects employing response biases or adopting guessing strategies. Although these criticisms have been aimed toward some of the language-based studies (Clifton, Kurcz, & Jenkins, 1965;Hayes-Roth & Hayes-Roth, 1977;James, Hillinger, & Murphy, 1977;Soli & Balch, 1976), none of them are warranted here.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In fact, the Bransford and Franks (1971) findings are difficult to replicate unless their methods are followed closely. Changes in presentation modality (Flagg & Reynolds, 1977; see also Katz & Gruenewald, 1974), in presentation of materials (Flagg, 1976;Flagg & Reynolds, 1977;Katz, Atkeson, & Lee, 1974), in instructions (James, Hillinger, & Murphy, 1977), and in testing procedures (Anderson & Bower, 1973;Griggs & Keen, 1977; greatly reduce or eliminate the integration effects found with the original Bransford-Franks paradigm. Finally, "integration" will occur for nonsemantic or arbitrary materials (e.g., letter-digits, nonsense syllables) if the original procedures are used (Flagg, 1976;Katz & Gruenewald, 1974;Reitman & Bower, 1973;Small, 1975).…”
Section: Integrationmentioning
confidence: 99%
“…For instance, if each acquisition sentence contained only one or two elements of a complex idea, test sentences containing three or four elements might be rejected as being inconsistent with the general style of the acquisition material. This was subsequently confirmed in several different investigations Flagg, 1976;Pezdek, 1978).Nevertheless, in the absence of any information about the specific acquisition sentences, and in the absence of any concomitant information about the general style of the acquisition material, James, Hillinger, and Murphy (1977) showed that the overall relationship between the subjects' responses and the number of elements in a test sentence was purely the result of variations in response bias. Such biases can apparently be overridden by appropriate experimental instructions; thus, the confidencerating function is essentially horizontal when subjects are required to judge whether test sentences have the same meaning as acquisition sentences (Katz, 1973;Moeser, 1975).…”
mentioning
confidence: 52%
“…Nevertheless, in the absence of any information about the specific acquisition sentences, and in the absence of any concomitant information about the general style of the acquisition material, James, Hillinger, and Murphy (1977) showed that the overall relationship between the subjects' responses and the number of elements in a test sentence was purely the result of variations in response bias. Such biases can apparently be overridden by appropriate experimental instructions; thus, the confidencerating function is essentially horizontal when subjects are required to judge whether test sentences have the same meaning as acquisition sentences (Katz, 1973;Moeser, 1975).…”
Section: The Constructive Theorymentioning
confidence: 99%